miR-96 Inhibits SV2C to Promote Depression-Like Behavior and Memory Disorders in Mice - Sun, Lidong; Bai, Donghao; Lin, Maoguang; Eerdenidalai,; Zhang, Li; Wang, Fengzhen; Jin, Shangwu (Frontiers in Behavioral Neuroscience, 2021)
Accumulating evidence continues to emphasize the role of microRNAs (miRNAs) as significant contributors to depression-like behavior and memory disorders. The current study aimed to investigate the mechanism by which miR-96 influences depression-like behavior and memory deficit in mice. A depression-like behavior and memory disorder mouse model was initially established by means of intraperitoneal injection with lipopolysaccharide (LPS). Memory deficits in the mice were evaluated using the New Object Recognition Test (NORT) and Morris water maze experiments, while the Sucrose Preference Experiment (SPT) and forced swimming experiments were performed to identify depression-like behavior in mice. The levels of TNF-α, MDA, SOD, GSH, and the monoamine transmitters 5-hydroxytryptamine (5-HT) and dopamine (DA) were subsequently detected in the serum. The expression of miR-96 and SV2C expression in the CA1 hippocampal region of the mice was evaluated by RT-qPCR and Western blot analysis. Finally, the relationship of miR-96 and SV2C was verified by dual luciferase reporter gene assay. Our data indicated that the expression of miR-96 was increased, while that of SV2C was decreased in the CA1 region of mice exhibiting depression-like behavior and memory impairment. When miR-96 was downregulated or SV2C was overexpressed via intra-cerebroventricular injection with miR-96 antagonist (miR-96 antagomir) or overexpression of SV2C vector, the NORT and sucrose preference index were increased, while the escape latency, number of water maze platform crossings, and the immobility time of the mice were decreased. The serum levels of TNF-α, IL-1β, and MDA in the mouse CA1 region of mice were reduced, while the levels of SOD and GSH were elevated following the downregulation of miR-96 or overexpression of SV2C. Collectively, our study demonstrates that miR-96 negatively regulates the expression of SV2C, which consequently leads to depression-like behavior and memory impairment in mice. Our findings highlight the potential of miR-96-targeted therapeutics.